2017
DOI: 10.5137/1019-5149.jtn.20575-17.1
|View full text |Cite
|
Sign up to set email alerts
|

The causes of post-operative meningitis: the comparison of gram-negative and gram-positive pathogens

Abstract: As conclusions; in NM, Gram-negative pathogens were seen more frequently; A.baumanni was the predominant pathogen; and NM caused by Gram negatives had worse clinical and laboratory characteristic and prognostic outcome than Gram positives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
33
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 24 publications
3
33
2
Order By: Relevance
“…No existing data comparisons on this topic were found in previous literature. Demirarslan et al previously investigated antibiotic treatment, reporting significantly higher rates of antibiotic usage and studies have reported Acinetobacter as the causative agent in as many as 30% of meningitis cases (15,19). Findings from the present study are in accordance with data from such studies.…”
Section: █ Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…No existing data comparisons on this topic were found in previous literature. Demirarslan et al previously investigated antibiotic treatment, reporting significantly higher rates of antibiotic usage and studies have reported Acinetobacter as the causative agent in as many as 30% of meningitis cases (15,19). Findings from the present study are in accordance with data from such studies.…”
Section: █ Discussionsupporting
confidence: 91%
“…No differences were observed regarding symptoms or clinical findings (headache, blurred consciousness or fever) upon diagnosis of POM between case and control groups. Similar findings were reported by Kurtaran et al when comparing POM with Gram (-) and Gram (+) bacterial growth (15).…”
Section: █ Discussionsupporting
confidence: 90%
See 3 more Smart Citations